A NEW APPROACH TO THE METHOD OF CARRYING OUT AEROBIC CLASSES WITH STUDENTS INSTITUTIONS OF HIGHER EDUCATION - Dronnikova Т.А. (Pedagogy of Higher and Secondary Education, 2004)
The article is devoted to the new methods take lessons of aerobic with in higher educational institutions.